Analisis Prediksi Kebangkrutan dan Tingkat Akurasi Model Zmijewski pada Perusahaan Industri Produk Perawatan Tubuh yang terdaftar di Bursa Efek Indonesia - Adi Katon Pamungkas; Irni Yunita (IPM2KPE, 2024)
The aim of this research is to understand the potential for bankruptcy that may occur in companies in the personal care products industry listed on the Indonesia Stock Exchange for the 2014-2022 period. This research method is a quantitative method with analysis techniques using the Zmijewski model. The research results show that 4 companies in the personal care products industry are predicted to be healthy and the Zmijewski model has a high level of accuracy of 100%. In conclusion, the four companies do not have the potential for bankruptcy in this period and the Zmijewski model can be a reliable tool in helping companies anticipate and manage financial risks that may arise in the personal care products industry. Keywords: Bankruptcy, Accuracy, Zmijewski